PROGRAM ANALYSIS AS A TOOL TO INCREASE THE EFFECTIVENESS OF BUDGET PLANNING: METHODOLOGY DEVELOPMENT ISSUES - A. I. Masterov (Финансы: теория и практика)
Today, Russia actively attempts to introduce the program-target approach in the budget planning process to improve the efficiency of budget resources management. However, the methodological framework of program budgeting is, as a matter of fact, missing in the Russian practice. This is particularly true when carrying out the planning and reviewing of government programs and key performance indicators required to build the program budgets.Based on the study of international experience with program budgeting, the article provides guidance for further development of approaches to the budgeting process. The article focuses on the issues of the development of alternative options for implementing objectives set in the government programs as well as the optimal choice from available options. The conducted analysis and the chosen course of actions make it possible to generate key performance indicators in the process of program budgeting. The article briefly describes the methods which are used in international practice. It points out that the same methods could be applied in Russia to work out the budget planning methodology. The article examines the «cost/performance» and «cost/benefit» methods which have been, and are still used in the program budgeting in the United States.The author identifies the main stages in the development and analysis of alternative options for building programs as well as a set of principles to be followed to develop government programs and find financing solutions.According to the author, observance of these principles would help improve the effectiveness of budget planning carried out with the use of program-target approaches.